Child Labour : An Unseen Problem - Sanjeev Kumar Yadav and Dr. IIa Arora (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Child labour has been a serious problem for many decades and a major challenge for many developing countries. It has existed for centuries not only in the poor sections of developing countries but also in developed countries in the 20th century. Many countries have made various laws and taken serious steps to eliminate child labour, yet this problem is very widespread throughout the world. The reasons for the incidence of child labour in India are complex and deeply rooted in the society. Poverty seems to be the main reason. Child labour can be found in both urban and rural areas. But child labour is more prevalent in rural areas because poverty is more prevalent in rural areas. However, many poor rural families struggle for a better life in urban areas. Poverty forces families to put their children to work to increase family income and ensure survival. The purpose of this paper is to analyse child labour in India. The findings show that child labour was a serious evil for the developing country India. But now according to the 2011 census report, there has been a decline in the total number of working children in the country.